On Statistical Boundedness of Metric Valued Sequences (European Journal of Pure and Applied Mathematics, 2012)
In this work, statistical boundednessÂ  is defined in a metric spaceand, statistical boundedness of metric valued sequences and theirsubsequences are studied. The interplay between the statisticalboundedness and boundedness in a metric spaces are also studied, andit is shown that boundedness imply statistical boundedness and ifthe number of elements of the metric space is finite then these twoconcepts coincide. Moreover, here is given analogy ofBalzano-Weierstrass Theorem.